Sexual violence in a digital age - Powell, Anastasia (Palgrave Macmillan, 2017)
This book examines how digital communications technologies have transformed modern societies, with profound effects both for everyday life, and for everyday crimes. Sexual violence, which is recognized globally as a significant human rights problem, has likewise changed in the digital age. Through an investigation into our increasingly and ever-normalised digital lives, this study analyses the rise of technology-facilitated sexual assault, 'revenge pornography', online sexual harassment and gender-based hate speech. Drawing on ground-breaking research into the nature and extent of technology-facilitated forms of sexual violence and harassment, the authors explore the reach of these harms, the experiences of victims, the views of service providers and law enforcement bodies, as well as the implications for law, justice and resistance. Sexual Violence in a Digital Age is compelling reading for scholars, activists, and policymakers who seek to understand how technology is implicated in sexual violence, and what needs to be done to address sexual violence in a digital age
Keywords: Gewalt; Frau; Stalking; Mobile Telekommunikation; Sexuelle Belästigung; Informationsgesellschaft; Cyber-Mobbing; Pornografie; Internet; Sex crimes; Online sexual predators; Sexual harassment; Cyberstalking; Internet pornography; Computer crimes